2021
DOI: 10.22541/au.161324350.06772360/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Home Accident Cases Applying to The Pediatric Emergency Department during the Covid-19 Pandemic: What Did the Pandemic Change?

Abstract: Background: Whether the pandemic caused an increase in the number of home accidents (HA) admitted to the pediatric emergency department (PED) was investigated. Applications in a similar quarter in 2019 and 2020 were compared. Methods: The study was retrospective. Their demographic data, the reason for admission to the hospital, the time of admission, the length of hospital stay, intensive care rate, and interventional procedures were recorded. The two groups were compared to find whether there was any differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
2
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
0
2
4
Order By: Relevance
“…Mann et al (2021) found that burns in children aged 2-3 years is less prevalent than other types of accident (45%).25 Unlike our results; according toGüleryüz et al (2021), the incidence of falls, stomach/intestinal foreign bodies, and stab wounds (in Türkiye) were significantly higher during the COVID-19 period among children26 . Similarly, Liguro et al (2021) report that ingestion/breathing of foreign bodies and burns were more frequently diagnosed in children who presented to the pediatric emergency department during the pandemic period15 Chaiyachati et al (2020).…”
contrasting
confidence: 72%
“…Mann et al (2021) found that burns in children aged 2-3 years is less prevalent than other types of accident (45%).25 Unlike our results; according toGüleryüz et al (2021), the incidence of falls, stomach/intestinal foreign bodies, and stab wounds (in Türkiye) were significantly higher during the COVID-19 period among children26 . Similarly, Liguro et al (2021) report that ingestion/breathing of foreign bodies and burns were more frequently diagnosed in children who presented to the pediatric emergency department during the pandemic period15 Chaiyachati et al (2020).…”
contrasting
confidence: 72%
“…Es probable que esta reducción sea por diversos factores, tales como el uso de cubrebocas, aumento en la frecuencia del lavado de manos y el distanciamiento social. 9 Lo anterior se relaciona con el hecho de la reducción de pacientes con infecciones respiratorias, ya que disminuyeron hasta en 80%. Este porcentaje no es muy diferente al reportado en otros países, tanto para infecciones respiratorias, 7,8,13,14 como gastrointestinales.…”
Section: Discussionunclassified
“…El confinamiento afectó de distintas formas la salud de los niños y adolescentes, en particular, redujo la transmisión de enfermedades infecto-contagiosas (como era la meta de las autoridades), dada la escasa convivencia con sus pares, aunado al incremento en la frecuencia y calidad de las medidas higiénicas. [6][7][8][9] Pero, también el confinamiento pudo tener repercusión en los accidentes intradomiciliarios; los informes, en general, indican aumento de los accidentes en niños durante la pandemia. [7][8][9] Una forma indirecta de evaluar el impacto del confinamiento de los niños sobre su salud física es la revisión de las solicitudes de atención médica en los servicios de urgencias.…”
Section: Wwwmedigraphicorgmx Introducciónunclassified
See 2 more Smart Citations